Optimization of number of base station antennas in downlink massive MIMO and analysis of imperfect channel state information by perfection factor - Ramisetty, Uma Maheswari; Chennupati, Sumanth Kumar (Engineering science and technology, an international journal, 2020)
In the present days, there is a rapid growth of data rates in wireless communication but suffers from channel state errors due to imperfections in channel state information (CSI) which leads to a decrease in energy and spectral efficiency. In this paper, the perfection factor has been proposed to optimize the number of base station antennas in massive MIMO and also for the reduction of channel estimation errors in CSI. This perfection factor calculates the achievable sum-rate which in turn determines the ratio of the number of base station antennas with respect to the number of users and further critical reliability. As critical reliability decreases the transmitted power reduces and the number of base station antennas is decreased. Simulation is carried out Massive MIMO System and the degree of perfection, energy efficiency, spectral efficiency are been evaluated. The effectiveness of the proposed method is tested with a different number of base station antennas and the number of users and also on with the increase imperfection CSI. The results obtained are presented and analyzed.